Kreatifitas Guru Mata Pelajaran Bahasa Indonesia Dalam Pemanfaatan Media Pembelajaran di SMA Negeri 7 Kepulauan Sula - Masuku, Mardiani (Peneliti.net, 2024)
This study aims to evaluate teachers' creativity in utilizing learning media at SMA Negeri 7 Kepulauan Sula. In this context, learning media is an important tool to enhance the effectiveness of learning and overcome learning challenges. Various previous studies have shown that teachers' creativity in utilizing learning media has a positive impact on students' learning outcomes. The research method used is field research with a descriptive qualitative approach, involving observation, interviews, and documentation as data collection techniques. Data analysis is conducted using qualitative data analysis techniques, with stages of data reduction, data presentation, and verification or conclusion drawing. The conclusions of this study are expected to provide useful input for schools and students in improving the utilization of learning media as teaching materials.